(untitled) (Research, Society and Development, 2021)
This article aims to develop and validate a scale on the maternal guilt regarding consumption and its correlation with self-esteem. The guilt theme has been studied in human and social science contributing to a psychosocial assessment or psychological development in terms of the person’s emotional structure and organization in the face of the desire to consume. In this way, focusing on the topic of consumer behavior, it is evaluated how much the mothers feel guilty for meeting or not complying with their children’s purchase order, thus allowing them to present a measure of psychological evaluation that is still scarce in the Brazilian context. 606 mothers, with children over 8 years old, participated in the study, distributed in three samples throughout Brazil. They answered the scale of guilt towards consumption for their children, self-esteem scale and sociodemographic data. It was observed that the scale is not only reliable, but that it is possible to evaluate two dimensions of the mother’s guilt: feeling of guilt due to ego mismatch and impulsivity and feeling of cathartic / unconscious guilt. In general, the quality of a measure about guilt in consumption for children was evidenced, as well as, that it is possible to use such measure for therapeutic and social contexts when it is intended to assess maternal consumption behavior.